Effect of doxycycline in gel form on bone regeneration: Histomorphometric and tomographic study in rat calvaria - Silva, Amanda C.; Oliveira, Marina R.; Amaral, Lysandro F. A.; Ferreira, Sabrina; Garcia, Idelmo R.; Mariano, Ronaldo C. (Wiley, 2016)
Background: This study aims to investigate the effects of the local application of doxycycline in the form of natrosolbased gel on bone regeneration by examining critical defects in rat calvaria. Methods: Twenty-four rats were randomly divided into three groups with eight animals each, according to the treatment received: BC (untreated, filled with blood clot), NAT (natrosol gel alone), and DOX (10% doxycycline gel). Four animals from each group were euthanized at 4 and 8 weeks postoperatively. In tomographic analysis, mean density in the region of the defect was calculated as a percentage relative to the native bone density. In histomorphometric analysis, the newly formed bone area was calculated as a percentage of the total area. The values obtained underwent analysis of variance and Tukey testing (P <0.05). Results: The mean percentage of tomographic density in the region of the defect at the end of 8 weeks was higher for DOX (44.37%), and statistical differences in this period were observed between DOX and NAT (33.10%) and DOX and BC (32.43%). Regarding new bone formation, at the end of 8 weeks, DOX (61.11%) also had the highest mean bone formation, and statistical differences were observed between DOX and NAT (34.61%) and DOX and BC (23.11%). Conclusion: It was observed that 10% doxycycline gel had a good effect on bone regeneration regarding the filling of critical defects in rat calvaria.
Keywords: Biocompatible materials; Bone regeneration; Cone-beam computed tomography; Doxycycline; Tissue engineering; Tissue scaffolds